PENGARUH KEPEMIMPINAN KEPALA MADRASAH TERHADAP KINERJA GURU UNTUK MEWUJUDKAN PRESTASI BELAJAR SISWA DI MTS PERSIS CIBATU KABUPATEN GARUT - Iman Nurjuman; Endang Soetari; Aceng Ulumudin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of principal leadership and teacher performance on student learning achievement at MTs Persis Cibatu Garut, addressing the decline in exam scores and low affective dimensions. A descriptive-analytical quantitative approach was employed. The research population included all teachers, utilizing validated and reliable questionnaire instruments. Data analysis involved simple and multiple linear regression, alongside classical assumption tests. Principal leadership (74.44%), teacher performance (83.22%), and learning achievement (73.77%) are in the good category. Leadership has a significant effect on teacher performance (R² = 13,9%) and learning achievement R² = 47,2%, Beta = 0,687). Teacher performance also has a significant effect on learning achievement (R² = 47,2%, Beta = 0,687). Simultaneously, both variables contribute 64.2% to student learning achievement F calculated = 25,947 > F table = 3,15 This phenomenon confirms that managerial collaboration and optimization of teachers' pedagogical competence are the ultimate keys to boosting graduate quality. This study provides a specific empirical mapping for private Islamic schools, identifying transactional leadership aspects and students' affective dimensions as critical operational points that require sustained strategic interventions.